Effect on vibration characteristics of fiber metal laminates sandwiched with natural fibers. (2020) - Kali, Naresh; Pathak, Sandeep; Korla, Srikanth
Abstract: Fiber Metal Laminates (FMLs) are composite materials in which fiber laminates are sandwiched between light weight metallic layers. A significant number of studies have been conducted on FMLs based on aluminum alloys sandwiched with commercially available fibers (glass fibers, carbon fibers and aramid fibers). However, studies on FMLs developed using natural fibers such as bamboo (B) and jute have not been explored to a great extent. In this article, three different FML specimens (Al/CF/Al/CF/Al, Al/CF/B/CF/Al, and Al/GF/B/GF/Al) are developed and their vibration characteristics are investigated. Comparative studies are conducted on the acceleration behavior of the vibrating specimens in time-domain. Furthermore, the results are studied in frequency-domain to analyze the shift in peak frequencies for the FMLs developed in this work. It is noticed that there is a significant fall in the peak acceleration when central aluminum laminate is replaced with a bamboo strip of a similar dimension.